My father$1 (Bs dragon s - Gannett, Ruth Stiles; Gannett, Ruth Chrisman (New York : Knopf : Distributed by Random House, 1987)
A young boy determines to rescue a poor baby dragon who is being used by a group of lazy wild animals to ferry them across the river on Wild Island.
"Borzoi spinters"--P. 4 of cover.
Keywords: Dragons -- Fiction; Animals -- Fiction